Coagulation and Fibrinolysis Indicators and Placental Malaria Infection in an Area Characterized by Unstable Malaria Transmission in Central Sudan. (30th July 2015) - Mostafa, Amged G.; Bilal, Naser E.; Abass, Awad-Elkareem; Elhassan, Elhassan M.; Mohmmed, Ahmed A.; Adam, Ishag
Abstract : This study aimed to investigate coagulation, fibrinolysis indicators, and malaria during pregnancy. Methods . A cross-sectional study was conducted at Medani, Sudan. Sociodemographic characteristics were gathered from each parturient woman (163) and malaria was investigated by blood film and placental histology. Protein C, protein S, antithrombin-III, tissue factor pathway inhibitor (TFPI), and plasminogen activator inhibitor-1 levels (PAI-1) were measured using ELISA. Results . One (0.6%), three (1.8), and 19 (11.7%) of the placentae showed active, chronic, and past infection on a histopathological examination, respectively, while 140 (85.9%) of them showed no signs of malaria infection. While the mean [SD] of the protein C, antithrombin-III, and TFPI was significantly lower, there was no significant difference in protein S and PAI-1 levels in women with placental malaria infection (n = 23 ) compared to those without placental malaria infection (140). In linear regression, placental malaria infection was associated with antithrombin-III. There was no association between placental malaria infections and protein C, protein S, TFPI, and PAI-1 levels. There was no association between hemoglobin, birth weight, and the investigated coagulation and fibrinolysis indicators. Conclusion . This study showed significantly lower levels of protein C, antithrombin-III, and TFPI in women with placental malaria infections.